Essentials of business law - Liuzzo, Anthony L.; Hughes, Ruth C. (McGraw Hill, 2022)
"The new, eleventh edition of the Essentials of Business Law program is a practical, concise, and broad-based introduction to the vibrant field of business law. While continuing to offer all of the features that have made the ten prior editions successful, this new edition includes a chapter on the areas of law affected by social media, updated content, and enhanced support materials. Both the traditional areas of law, such as contracts and property, and the emerging areas of law, such as e-commerce and environmental, are covered in short, informative chapters written to capture the essence of each topic. The objective of the text throughout its coverage is ease-ease of use, ease of teaching, ease of assessment, and ease of understanding. It has been developed for those seeking a more fundamental overview of the concepts and principles that are vital to the understanding of business law"--Provided by publisher.